A CRITICAL ANALYSIS OF H G WELLS’ ANTICIPATIONS IN EXPLORING THE MECHANISM OF FUTURISTIC PREDICTIONS - Jose, Bijesh V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The ambiguity surrounding what lies ahead is precisely what draws human beings to prognostications of the future, which may not be explicable through rational principles. Occasionally, Futuristic predictions have an equitably likely chance of being either accurate or inaccurate. However, the exact predictions can inspire a sense of awe within the human psyche. Despite the seemingly low prior probability of many such events occurring, they nonetheless transpire. The mere difficulty in comprehending the causal mechanisms behind such occurrences does not render them nonexistent. Out of all the literary luminaries in the English language, Herbert George Wells stands out for his remarkable ability to astound the global populace with his visionary predictions that have materialized with remarkable and startling accuracy. Wells’ unparalleled ability to predict the future is most prominently showcased in his seminal work, Anticipations (1901) which demonstrate his mastery of political realism and uncanny prophetic insight. A scrutiny of Anticipations is made to explore the compendium of futuristic predictions in it.